2004
DOI: 10.1111/j.0904-2512.2004.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA typing in Taiwanese patients with oral submucous fibrosis

Abstract: We conclude that some Taiwanese areca quid (AQ) chewers with particular HLA phenotypes and haplotypes are prone to have OSF. In addition, some particular HLA haplotypes may play more important roles than the individual HLA phenotypes for the genetic susceptibility to OSF. However, the significantly increased HLA phenotype B76 and three of the common HLA haplotypes detected are present in only about 20% of incident cases of OSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…Rapid development of OSMF in young adults or even children reported in clinical case reports further adds weight to this believe . HLA typing has shown certain HLA antigens with a significantly raised frequency in OSMF .…”
Section: Discussionmentioning
confidence: 86%
“…Rapid development of OSMF in young adults or even children reported in clinical case reports further adds weight to this believe . HLA typing has shown certain HLA antigens with a significantly raised frequency in OSMF .…”
Section: Discussionmentioning
confidence: 86%
“…[9] demonstrated that some Taiwanese betel‐quid chewers with particular HLA phenotypes and haplotypes are prone to develop OSF. In addition, some particular HLA haplotypes may play more important roles than individual HLA phenotypes for the genetic susceptibility to OSF [5]. Our previous studies revealed that the HLA‐DQA1 and HLA‐DQB1 allele frequencies in breast cancer patients showed no significant differences from those of control groups.…”
Section: Discussionmentioning
confidence: 96%
“…Chen et al. [5] found a significant increase in the frequency of HLA‐B76 and haplotype HLA‐B48/Cw7, B51/Cw7, and B62/Cw7 in OSF patients.…”
Section: Introductionmentioning
confidence: 99%
“… Nutritional factors: iron and vitamin B12 deficiency has been implicated particularly in conjunction with other factors 15 Genetic disposition: an increased frequency of HLA 10, DR3 and DR7 has been noted in patients with OSF 15,16 Hormonal factors: there would appear to be a predisposition in females 13,15 …”
Section: Discussionmentioning
confidence: 99%